The Land Agent 1700-1920 - Rees, Lowri Ann (Edinburgh University Press, 2022)
Explores the role of land agents in Britain and its imperial territories between c. 1700-1920This book brings together leading researchers of British and Irish rural history to consider the role of the land agent, or estate manager, in the modern period. Land agents were an influential and powerful cadre of men, who managed both the day-to-day running and the overall policy direction of landed estates. As such, they occupy a controversial place in academic historiography as well as popular memory in rural Britain and Ireland. Reviled in social history narratives and fictional accounts, the land agent was one of the most powerful tools in the armoury of the British and Irish landed classes and their territorial, political and social dominance. By unpacking the nature and processes of their power, The Land Agent explores who these men were and what was the wider significance of their roles, thus uncovering a neglected history of British rural society.ContributorsDavid Gent, University of York Ewen A. Cameron, University of Edinburgh John MacGregor, Independent ScholarFidelma Byrne, Maynooth University Rachel Murphy, University College CorkFinlay McKichan, Independent Scholar Lowri Ann Rees, Bangor University Anne Casement, Independent Scholar Ciarán Reilly, Independent Scholar Shaun Evans, Bangor University Robin K. Campbell, Independent Scholar Kirsty Gunn, University of DundeeAnnie Tindley, Newcastle University
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: Scottish Studies; HISTORY / Europe / Great Britain / General; Land tenure -- Scotland -- Highlands -- History